The Prohibition of Eyelash Extensions for Women: A Study of Hadith Sahih Muslim, Index Number 2123 - Diva Rahayu Oktaviani; Muhid Muhid; Andris Nurita (Taqaddumi: Journal of Quran and Hadith Studies, 2023)
This article delves into the understanding of the hadith regarding the use of eyelash extensions for women, focusing on the implications of this practice. In today's society, women place great importance on their appearance, which has led to a surge in the popularity of various beauty enhancements. However, considering the hadith narrated by Muslim (index number 2123), wherein the Prophet forbade women from using hair extensions, it becomes crucial to gain a deeper understanding of the permissibility of eyelash extensions, particularly for women. To address this issue, a qualitative research approach is employed in this study, utilizing library research and content analysis methods. Through a thorough examination of relevant literature and scholarly discussions, the article aims to shed light on the interpretation and application of the hadith in the context of eyelash extensions. By examining the underlying reasons behind the prohibition and exploring any potential exceptions or considerations, this research seeks to contribute to a comprehensive understanding of the subject matter. The findings of this study provide valuable insights into the understanding of the hadith and its relevance to the use of eyelash extensions for women. This research highlights the need for a nuanced perspective, taking into account the evolving societal norms and personal preferences while remaining grounded in the teachings of Islam. Ultimately, this article serves as a resource for individuals seeking guidance on the permissibility of eyelash extensions, especially among Muslim women, in navigating contemporary beauty practices within the framework of Islamic principles.